La radiación ultravioleta como principal factor de riesgo para el carcinoma basocelular - Loaiza Cuenca, Gerardo Andrés (Machala: Universidad Técnica de Machala, 2023)
Introduction: Basal cell carcinoma (BCC) is a malignant epithelial neoplasm that has its genesis in the pluripotent cells of the epithelium, with slow development and local invasive capacity, it is the most common skin neoplasm, with about 80% of percentage of presentation worldwide, and our country is one of the highest incidence. UV radiation plays the most important role within the origin of CBC, in combination with other risk factors. The types of CBC can be aggressive or non-aggressive and based on that analysis the possible therapeutic options will be established. Objectives: To analyze the influence of exposure to ultraviolet radiation as the most important risk factor in the development of basal cell carcinoma, through literature review in high-impact scientific journals for primary prevention in the community. Methodology: An exhaustive search was carried out in journals and articles in databases such as Pubmed, Google Scholar, with 5 years old, related to exposure to UV radiation as the most important risk factor in the oncogenesis of basal cell carcinoma. Conclusion: UV radiation is directly related to the development of CBCs, exposure to radiation over time, increases the risk, especially in exposure to UVB radiation, because it produces genetic alterations and DNA damage that predispose to CBC carcinogenesis. Timely diagnosis and treatment prevents lesions from invading nearby structures and major complications from appearing.
Introducción: El carcinoma basocelular (CBC) es una neoplasia epitelial de carácter maligno que tiene su génesis en las células pluripotenciales del epitelio, con lento desarrollo y capacidad invasiva local, es la neoplasia de piel más común, con cerca del 80% de porcentaje de presentación a nivel mundial, y nuestro país es uno de los de mayor incidencia. La radiación UV juega el papel más importante dentro del origen del CBC, en combinación con otros factores de riesgo. Los tipos de CBC pueden ser agresivos o no agresivos y según ese análisis se establecerán las posibles opciones terapéuticas. Objetivos: Analizar la influencia de la exposición a la radiación ultravioleta como el factor de riesgo más importante en el desarrollo del carcinoma basocelular, mediante la revisión bibliográfica en revistas científicas de alto impacto para la prevención primaria en la comunidad. Metodología: Se realizó una búsqueda exhaustiva en revistas y artículos en bases como Pubmed, Google Scholar, con 5 años de antigüedad, relacionados con la exposición a la radiación UV como el factor de riesgo más importante en la oncogénesis del carcinoma basocelular. Conclusión: La radiación UV está directamente relacionada con el desarrollo de los CBC, la exposición a la radiación a lo largo del tiempo, aumenta el riesgo, sobre todo en la exposición a la radiación UVB, debido a que produce alteraciones genéticas y daño al ADN que predisponen a la carcinogénesis del CBC. El diagnóstico y tratamiento oportunos evita que las lesiones invadan estructuras cercanas y aparezcan complicaciones importantes.
Keywords: CARCINOMA BASOCELULAR; RADIACION ULTRAVIOLETA; EXPOSICION; FACTORES DE RIESGO